Motherhood in Socio-cultural Context A Critical Qualitative Study - Faezeh Gafari Sirizi; Abbas Askari Nodoushan; Ali Ruhani (مطالعات اجتماعی روان‌شناختی زنان, 2023)
In intergenerational family relationships, the respect for the role of the mother has always been emphasized in Iranian-Islamic culture. However, conducting socio-cultural research in Iran with a special focus on the roles of mothers is one of the research gaps that requires more scientific research. The purpose of this study is to examine the social and cultural concerns of mothers in familial and social relationships. The research method used was the critical qualitative method of Carspecken. Research data were collected through in-depth interviews with 15 mothers who had children under the age of two. Findings show categories such as physical and mental exhaustion of the mother, child developmental concerns, increasing needs with child growth, mother's sensitivity due to uncontrollable child, disturbance in housekeeping, gender preference, unstable social status of the mother, etc. were obtained. The results showed mothers' dissatisfaction and disturbance about some social and cultural structures that put pressure on them. Based on the results, there is a need to pass laws to facilitate and improve the supportive and emotional contexts for mothers. Also, the existing capability of Iranian society should be employed more effectively to maintain and promote the status of the mother as a proud role in Iranian-Islamic cul. ‌